ШАҢАРАҚТА ДЕНЕ ТӘРБИЯСЫНА ИТИБАР ҚАРАТЫЎДА АЛЫП БАРЫЛАТУҒЫН ЖУМЫСЛАР - Оразов, Ш.Б.; Қалжанов, П.; Қалжанов, Р. (FAN va JAMIYAT, 2018)
The article is devoted to the issues of physical education in the family. The author studied such notions as physical education, personal hygiene, neatness, eating in time and other habits in the family. There have been investigated the issues of children’s upbringing in the family, relation between parents and teachers, physical and mental development, family and school the influence of the community and pedagogical education on children. It is emphasized the necessity of creating conditions for children to play games after classes: running and other national games under the control of parents.